STRATEGI PENGEMBANGAN KARAKTER ANAK PADA KOMUNITAS PEDULI ANAK JALANAN (KPAJ) DI KELURAHAN BARA-BARAYA UTARA KECAMATAN MAKASSAR KOTA MAKASSAR - Inayah Nur Wulandari; Kartini Marzuki; Rudi Amir (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2023)
This study examines the Strategy for Children's Character Development in the Community Care for Street Children (KPAJ) in Bara-Baraya Utara Village, Makassar District, Makassar City. The purpose of this study was to determine the strategies used by educators in developing the character of the foster children. The subjects of this study were 6 people consisting of 3 educators and 3 fostered children. Data were collected through interviews, observation and documentation. Data is processed through data reduction, data presentation, and drawing conclusions. The results showed that there were 3 character development strategies used by educators, namely 1) Exemplary with the way educators behaved well in their activities such as speaking good words, saying help to fostered children when asking for help and saying thank you if they were helped 2) Cultivating discipline by making unwritten rules and giving rewards in the form of praise and punishment in the form of direct reprimands to the fostered children. 3) Habituation consists of activities carried out routinely such as greeting when entering the study house, reading prayers before and after studying, reading the Qur'an before learning begins, memorizing surahs every Saturday, shaking hands with educators and spontaneous activities by giving advice to foster children who do bad behavior, say tabe' when walking in front of older people, say please, sorry and thank you and say good.